2021
DOI: 10.1097/hjh.0000000000002794
|View full text |Cite
|
Sign up to set email alerts
|

Meal patterns and incident hypertension in community-dwelling middle-aged adults: an 11-year follow-up cohort study

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 39 publications
0
4
1
Order By: Relevance
“… 57 Compared with people whose dinner energy ratio was 30.2–39.1% (T2), a high dinner energy ratio (>39.1%) was related to an increasing prevalence of hypertension (adjusted OR 1.716; 95% CI, 1.302–2.261). A study on middle-aged adults showed that dinner energy ratio was not related to high blood pressure, 18 which was inconsistent with our results. This might be because their participants who had high dinner energy ratio always had low sodium intake, whereas the average daily sodium intake of our high dinner energy ratio population was high (5.2 g).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“… 57 Compared with people whose dinner energy ratio was 30.2–39.1% (T2), a high dinner energy ratio (>39.1%) was related to an increasing prevalence of hypertension (adjusted OR 1.716; 95% CI, 1.302–2.261). A study on middle-aged adults showed that dinner energy ratio was not related to high blood pressure, 18 which was inconsistent with our results. This might be because their participants who had high dinner energy ratio always had low sodium intake, whereas the average daily sodium intake of our high dinner energy ratio population was high (5.2 g).…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, we found a U-shaped relationship between dinner energy ratio and hypertension: compared with people whose dinner energy ratio was 30.2–39.1% (T2), a higher dinner energy ratio (>39.1%) was related to an increased prevalence of hypertension, and a lower dinner energy ratio (<30.2%) was also related to an increasing prevalence of hypertension (adjusted OR 1.371; 95% CI, 1.036–1.814). In China, the appropriate dinner energy ratio was considered to be 30–40%, 18 which was not evidence-based. Our study suggested that dinner energy ratio of 30.2–39.1% was relatively healthy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increasing correlation between significant variables might decrease the value of ORs. Second, the great socioeconomic and environmental transformations related to hypertension during 2011-2018, such as dietary patterns, exposure to fine particulate matter (PM 2.5 ), built environment factors, and some other confounders, were not controlled in our study [ 52 - 54 ]. Third, the association of midday napping with hypertension might be moderated by other variables such as physical conditions and night sleep duration [ 49 , 55 ].…”
Section: Discussionmentioning
confidence: 99%